21.8k views
3 votes
Look at the pic below an help pls

Look at the pic below an help pls-example-1
User Harishr
by
4.6k points

1 Answer

11 votes

Answer:

y=2/3(x-3)^2+1

Explanation:

The parent function of a parabola is y=x^2:

The transformation of this graph shows the parabola is shifted to the right 3 and up 1 so we apply that to our equation y=(x-3)^2+1

to solve the stretch factor:

y=a(x-3)^2+1

we can see when x=0 y=7 so we use this set

7=a(0-3)^2+1

7=a(-3)^2+1

-1 -1

6=9a

divide by 9

a=2/3

User Muhammad Nour
by
4.7k points